(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2024)
The text raises questions about the different meanings and variations that the expression ’political theater’ can generate in the contemporary theater scene, based on two operative notions: amphibious theater and aesthetic-political actions, examining their application in the Theory of Performing Arts and their implications for the construction of a recent History of Brazilian theater. Through a dialogical approach with the queer movement and decolonial studies, the article combines different types of analysis - literary, theatrical, sociological, political - to produce an interdisciplinary text at the crossroads of theater and the human sciences. Finally, the text does justice to the plurality of modes of production in contemporary political theater.